Okara waste as a substrate for the microalgae phaeodactylum tricornutum enhances the production of algal biomass, fucoxanthin, and polyunsaturated fatty acids - Kim, Jaejung (2023)
Despite the rich nutritional content of okara, the majority remains underutilized and discarded as food waste. In this study, solid-state fermentation of okara with food-grade fungi was performed to extract and solubilize any remnant nutrients locked within the lignocellulosic matrix to produce a nutrient-rich okara fermentate. Fermented okara media (FOM) was used as the sole nutrient source for growing marine diatom, Phaeodactylum tricornutum. Results have shown a two-fold increase in biomass production when grown on FOM (0.52 g L−1) as compared with conventional Guillard’s F/2 media (0.25 g L−1). Furthermore, cellular fucoxanthin content was enhanced significantly by two-fold to reach a final concentration of 15.3 mg g−1 compared to 7.3 mg g−1. Additionally, a significantly higher amount of polyunsaturated fatty acid (PUFA) was produced, particularly eicosapentaenoic acid (EPA) which yield has increased by nearly three-fold. Metabolomics analysis of intracellular contents in fermented okara culture revealed a significantly enhanced accumulation of nitrogenous metabolites, alongside the decrease in sugar metabolites as compared to F/2 culture, thus indicating metabolic flux towards pathways involved in cellular growth. This study demonstrated an innovative and low-cost strategy of using fermented okara as a nutritious substrate for achieving a sustainable media replacement for high density algal growth with a simultaneous enhancement of production in highly valued nutraceuticals, including fucoxanthin and EPA.